Prevalence Of Negative Perception Of Self-Care Among Brazilian Older Adults Living In The Community And Associated Factors - Thaila Maki Hiraga; Samila Sathler Tavares Batistoni; Flávia Silva Arbex Borim; Anita Liberalesso Neri (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To describe and identify sociodemographic factors and health behaviors associated with a negative perception of self-care in community-resident older adults in seven Brazilian cities. METHODS: This is a cross-sectional analysis of data from the Frailty in Brazilian Older Adults (FIBRA) study. Sociodemographic characteristics, health-related behaviors, and perception of self-care in health were assessed. For analysis, percentage distributions and respective 95% confidence intervals were estimated, at a significance level of 5%. Univariate and multivariate logistic regression analyses were carried out, with stepwise variable selection. RESULTS: Of 2,552 older adults in the overall sample, most (65.8%) were women, with a mean age of 72.3 ± 5.5 years. The worst perception of self-care was associated with non-use of dental care services (OR = 1.48, p < 0.001), income range from 1.1 to 3 times the minimum wage (OR = 1.46, p = 0.049), smoking (OR = 1.41, p = 0.030), sedentary lifestyle (OR = 1.32, p = 0.003), and male gender (OR = 1.24, p = 0.023). CONCLUSION: Although no high frequencies of negative health behaviors were found, the association of poor perception of self-care with modifiable factors, such as sedentary lifestyle and smoking, stands out. Failure to seek dental care continues to be a challenging aspect among the elderly. These results point to a potential subjective indicator for clinical and health research surveys throughout the aging process.